Alteraciones morfofisiológicas de la sub mucosa muscular del sistema gastrointestinal bajo en caninos - Sandoval Romero, Bryan Ismael (2023)
Dogs experiencing digestive problems may exhibit clinical sympotms such as vomiting and diarrhea. These symptoms can arise due to various factors, including food intolerance, ingestion of foreign objects leading to gastrointestinal obstruction, infections, and inflammation. These factor can induce structural changes in the intestine, thereby impacting its normal functionality. The objective of this research was to analyze alterations in the thickness of the submucosal and muscular layers of the intestinal wall in the duodenum, jejunum, ileum, and colon of dogs displaying signs of the observed disorders. The study encompassed 25 canines displaying symptoms of comiting and diarrhea attributed to nutritional food types. Through abdominal ultrasound conducted across cranial, medial, and caudal abdominal regions, measurements were obtained per segment and general dimensions for each intestinal segment. This methodology gratly facilitated dimension acquisition for the aforementioned intestinal segments and respective layers, including serosal and mucosal layers, thereby revealing altered measurements for the gastrointestinal segments acroos each layer. Notably, each of the aforementioned pathologies emerged due to the type of diet provided to the pets, encompassing both homemade and commercially balanced foods. Additionally, case were documented where patients exhibited no symptoms or gastrointestinal alterations.